2005
DOI: 10.1097/01.brs.0000164136.95885.e7
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pedicle Screw Placement With or Without Application of Compression Across the Neurocentral Cartilage on the Morphology of the Spinal Canal and Pedicle in Immature Pigs

Abstract: Sagittal spinal alignment is found to be changing as a child grows. There is a statistically significant difference among different age groups, especially at cervicothoracic, thoracolumbar, and lumbosacral junctions. The position of the sacrum (inclination and translation), and spatial orientation, as well as the global magnitude of thoracic kyphosis, and lumbar lordosis changes with growth. These findings should be taken into consideration for the young patients who require spinal instrumentation. The questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 21 publications
2
61
0
1
Order By: Relevance
“…In immature animals experiment, it has been shown that vertebral growth is retarded by inhibition of the NCC. The pedicle screws have an influence in development on symmetry and canal parameters [13][14][15]. The consistent findings of negative effects imparted upon pedicle growth in these previous animal studies have increased the concerns that pedicle screws used in young children might result in similar problems.…”
Section: Introductionmentioning
confidence: 48%
See 1 more Smart Citation
“…In immature animals experiment, it has been shown that vertebral growth is retarded by inhibition of the NCC. The pedicle screws have an influence in development on symmetry and canal parameters [13][14][15]. The consistent findings of negative effects imparted upon pedicle growth in these previous animal studies have increased the concerns that pedicle screws used in young children might result in similar problems.…”
Section: Introductionmentioning
confidence: 48%
“…It allows a short fusion and the preservation of motion segments because of a rigid segmental stabilization. In spinal deformities surgery, segmental transpedicular instrumentation provides a superior correction of deformity in the coronal, sagittal, and transverse planes [13]. In pediatric scoliosis, there is no other chance to get a firm anchorage for correction and stabilization.…”
Section: Discussionmentioning
confidence: 99%
“…The measurements included the inner and outer pedicle diameters on the transverse plane, pedicle sagittal diameter, pedicle length and the pedicle angle on the transverse. (1) Pedicle diameters on the transverse plane decreased gradually from T1 to T4 and increased gradually from T5 to T12. The shortest transverse diameter of the thoracic pedicle was T4 or T5.…”
mentioning
confidence: 99%
“…One previous study suggests injury to the NCS or application of compressive forces across the NCS results in iatrogenic spinal stenosis in an animal model [2]. Using a histomorphometric analysis in an 8-week-old pig model, Zhang and Sucato demonstrated unilateral pedicle NCS screws do not lead to narrowing of the total spinal canal area [18].…”
Section: Discussionmentioning
confidence: 99%